Loss of von Willebrand factor high-molecular-weight multimers at acute phase is associated with detectable anti-ADAMTS13 IgG and neurological symptoms in acquired thrombotic thrombocytopenic purpura. Issue 181 (September 2019) - Béranger, Nicolas; Benghezal, Sandrine; Savigny, Sylvaine; Capdenat, Sophie; Joly, Bérangère S.; Coppo, Paul; Stepanian, Alain; Veyradier, Agnès
Abstract: Introduction: Thrombotic thrombocytopenic purpura (TTP) is a rare life threatening thrombotic microangiopathy caused by a severe functional deficiency of ADAMTS13, most frequently due to autoantibodies to ADAMTS13, thus termed acquired autoimmune TTP. ADAMTS13 specifically regulates the adhesive activity of von Willebrand factor (VWF) by cleaving its high-molecular-weight multimers (HMWM). We investigated whether VWF-HMWM level at acute phase of TTP could be a predictive factor for morbidity. Material and methods: We gathered clinical and biological data from a cohort of 114 patients with acquired TTP at acute phase. VWF-HMWM were assessed by electrophoretic analysis and by an ELISA measuring the capacity of VWF to bind to collagen (VWF:CB), and linear correlation between these two methods was carried out. We cross-referenced clinical and biological data with VWF-HMWM levels. Results: VWF-HMWM levels were heterogeneous, but half of our patients were below normal range (50% if assessed by electrophoresis; 47.4% if assessed by ELISA). The correlation study between electrophoresis and ELISA reached statistical significance (r 2 = 0.5979; p < 0.0001). Statistical analysis showed that loss of VWF-HMWM as assessed by VWF:CB < 70 IU/dL is associated with detectable anti-ADAMTS13 antibodies, severe neurological symptoms and thrombocytopenia ( p < 0.05). Conclusion: Our results confirm that VWF-HMWM can be satisfactorily assessed by VWF:CB, much easier to perform than electrophoresis. The association highlighted between loss of VWF-HMWM, detectable anti-ADAMTS13 IgG and neurological symptoms may offer new insights to understanding the pathophysiology of acquired auto-immune TTP. Highlights: VWF collagen binding assay is efficient to assess VWF high molecular weight multimers. Loss of VWF high molecular weight multimers is linked to detectable anti-ADAMTS13 IgG. Loss of VWF high molecular weight multimers is associated with severe autoimmune TTP. VWF high molecular weight multimers are predictive of clinical presentation in TTP. Microthrombi could form more rapidly in autoimmune TTP than in non-autoimmune TTP.